IMPROVING THE METHODOLOGY FOR RAISING THE OVERALL ENDURANCE OF GIRLS OF THE UPPER CLASS IN ATHLETICS CLUBS AT SCHOOL - Qazokov Sodiq Ramazonovich (TADQIQOTLAR, 2025)
Abstract:  Athletics  is  very  important  for  developing  endurance  and  fitness among  sports.  Increasing  the  overall  endurance  of  high  school  girls  will  further increase their interest in physical health and sports. This article presents suggestions for improving the methodology of endurance training in athletics circles.